A Diagnostic Dilemma of Recurrent Disseminated Peritoneal Leiomyomatosis with Hypertrophied Omental Vessels: Imaging and Embolization of Omental Branches with Positive Outcome - Jitendra Parmar; Chander Mohan; Deepak Hans; Maulik Vora (Case Reports in Obstetrics and Gynecology)
We present a case report of recurrent disseminated peritoneal leiomyomatosis in a 30-year-old female with a past history of laparoscopic myomectomy by a technique of morcellation for a large fibroid in 2014. After one year she presented in 2015 with a well-defined oval shaped fibroid along the anterior abdominal wall, which was supplied by the 10th intercostal artery and a branch of right internal mammary artery. She was again presented after 1 year in 2016 with a large pelvic-abdominal fibroid with blood supply from the omental artery, a branch from the right gastroepiploic artery, and sigmoid branches of inferior mesenteric artery.